A multi-functional converter based switched reluctance motor drive for electric vehicle - Dungrothu Kalpana; Malligunta Kiran Kumar; Pidikiti Tripura (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Owing to the resilience and ease of control, switched reluctance motors are commonly utilized in electric vehicle drives. This paper provides a topology for a multi-functional power converter for switched reluctance motor based electric vehicle drive with driving, braking and charging potentialities. With efficient control algorithms, a single power electronic converter is used for motoring, regenerative braking, and charging of the battery bank, resulting in a cost-effective power electronic interface. The front-end voltage control and current control of the switched reluctance motor (SRM) are used to achieve open loop and closed loop speed control during driving mode. Re-generation is made possible through restricted switching of phases in negative torque region. A bridgeless rectifier converter is built in battery charging mode by combining the SRM's two-phase windings with the prevailing power devices of an integrated power converter, eliminating the need for additional inductors and charging units. Simulations are run in MATLAB/Simulink, and simulation results are used to validate the control schemes for all modes.